Dissipation of endosulfan in field-grown tomato (Lycopersicon esculentum) and cropped soil at Akumadan, Ghana - Ntow, W.J.; Ameyibor, J.; Kelderman, P.; Drechsel, Pay; Gijzen, H.J. (2007)
The dissipation and persistence of endosulfan (6,7,8,9,10,10-hexachloro-1,5,5a,6,9,9a-hexahydro- 6,9-methano-2,4,3-benzodioxathiepin 3-oxide) applied to field-grown tomato (Lycopersicon esculentum) were studied at a vegetable-growing location in Ghana. Plant tissue samples and cropped soil collected at 2 h-14 days and 8 h-112 days, respectively, after application, were analyzed by gas chromatography-electron capture detection (63Ni) to determine the content and dissipation rate of endosulfan isomers (R- and _-endosulfan) and the major metabolite, endosulfan sulfate. After two foliar applications of commercial endosulfan at 500 g of active ingredient/hectare, the first-order reaction kinetic was confirmed to describe the dissipation of endosulfan residues in tomato foliage and cropped soil. However, functions that best fit the experimental data were the biphasic process for foliage and the monophasic process for cropped soil. Calculated DT50 and DT90 values for endosulfan residues in cropped soil were not significantly (p < 0.05) different for each of the two isomers.